Teacher Support and Student Well-Being In Secondary Education: A Systematic Literature Review - Zainab Zukhrufa; Kurniawati, Farida (Psikologika: Jurnal Pemikiran dan Penelitian Psikologi, 2026)
Student well-being in secondary education is facing a global decline amidst the vulnerable transition of adolescence, which is prone to mental health issues. While previous studies have predominantly highlighted teacher support in the context of academic engagement, its specific role in psychological well-being remains under-synthesized comprehensively. This study aims to investigate the mechanism of teacher support as a vital predictor of student well-being. Employing a Systematic Literature Review (SLR) method following PRISMA 2020 guidelines, a search across Taylor & Francis, Scopus, and ScienceDirect databases for articles published between 2019–2025 yielded 9 empirical studies meeting the inclusion criteria. Data synthesis reveals that teacher support consistently serves as a positive predictor operating through two main mechanisms: a full role as a secondary attachment figure providing emotional security, and a partial role mediating the formation of class cohesion and students' social-emotional competence. In crisis contexts, teachers function as stability anchors reducing students' existential fears. These findings underscore the teacher's position as a protective factor for vulnerable students. This study offers critical implications for developing school interventions that extend beyond pedagogy to prioritize the quality of teacher-student interpersonal relationships.